O povo, os juízes e a polícia : histórias de abuso de poder policial na Bahia 1900-1920 - Barbosa, Alisson Gonçalves (2014)
This study aims to analyze actions of conduct by law enforcement authorities against segments of the Bahian population between the years 1900 and 1920, besides highlighting the different forms of reaction against these same practices that society considered abusive. For this it was necessary to understand the universe of police activity, observing their daily actions to combat crime, and show under what conditions was done police work and what it meant to be a cop, both economically, and socially in the period investigated. The soldiers crowded the ranks of the corporation had a popular origin, which meant that the agents can order carregassem habits and customs that often clashed with the ideals of modernity and civility rendered by the ruling classes of the time.